2017
DOI: 10.1136/injuryprev-2017-042542
|View full text |Cite
|
Sign up to set email alerts
|

Ethical considerations for the design and implementation of child injury prevention interventions: the example of delivering and installing safety equipment into the home

Abstract: We conclude that this intervention is justifiable from an ethical perspective but that this type of reflection loop is helpful to identify the impact of interventions beyond effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Research studies have shown that although fewer children die of infectious and chronic diseases these days, more mortalities have been globally reported as a result of injuries 33. Therefore, prevention of injury should be an integral part of public health 34. This study demonstrated that three categories of factors contribute to house injuries.…”
Section: Discussionmentioning
confidence: 65%
“…Research studies have shown that although fewer children die of infectious and chronic diseases these days, more mortalities have been globally reported as a result of injuries 33. Therefore, prevention of injury should be an integral part of public health 34. This study demonstrated that three categories of factors contribute to house injuries.…”
Section: Discussionmentioning
confidence: 65%
“…Today, in the age of globalization and the internet, we would sketch another landscape of the Leviathan including cellphones, autos, computers, robots and cobots (companion robots). A growing number of corporate persons populate our human biotopes, among them the FAANG's (Facebook, Amazon, Alibaba, Netflix, Google); but there are still the old corporate industrial neighbors such as General Motors, Nestle, Siemens.Hospitals are corporate neighbors as well and in order to be respected and gratefully honored, they have to develop flexible and adaptable internal and external interactions 43. Corporate health care providers are integrated in their social biotope,40 Tao Te Ching 11.41 In European culture it was Christine de Pizan, a poet and philosopher, at the Court of Charles V of France, considered to be one of the first feminists, who wrote the book 'Livre du Corps Policie', -Book of the Body Politic -in 1407.…”
mentioning
confidence: 99%